2023
DOI: 10.3390/ma16020697
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Toughness of Engineered Cementitious Composites with Desert Sand

Abstract: In this paper, engineered cementitious composites (ECCs) were prepared with desert sand instead of ordinary sand, and the toughness properties of the ECCs were studied. The particle size of the desert sand was 0.075–0.3 mm, which is defined as ultrafine sand. The ordinary sand was sieved into one control group with a size of 0.075–0.3 mm and three other reference groups. Together with the desert sand group, a total of five groups of ECC specimens were created. Through a uniaxial tensile test, three-point bendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Due to the finite nature of this resource and its environmental impact, the urgent need for alternative materials is particularly prominent. Research has been conducted to explore the use of local materials in preparing ECC [ 28 , 29 ]. Using seawater and coral sand as the primary components of SCECC materials can fully leverage the advantages of ECC, including high ductility, durability, blast, and impact resistance while fully using marine resources.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the finite nature of this resource and its environmental impact, the urgent need for alternative materials is particularly prominent. Research has been conducted to explore the use of local materials in preparing ECC [ 28 , 29 ]. Using seawater and coral sand as the primary components of SCECC materials can fully leverage the advantages of ECC, including high ductility, durability, blast, and impact resistance while fully using marine resources.…”
Section: Introductionmentioning
confidence: 99%
“…In total, eleven research papers and six reviews have been collected. Considering the high interest in this field for finding alternatives for virgin raw materials, in the research article conducted by Lv, Z. et al [ 1 ], an interesting experimental study was conducted on the effect of replacing ordinary sand with desert sand on the obtainment and characterization of engineered cementitious materials. Additionally, A. İ. Çelik et al [ 2 ] observed that a 20% replacement of fine aggregates and coarse aggregates with recycled crushed glass resulted in a significant increase in the mechanical properties of concrete.…”
mentioning
confidence: 99%